Moral education in pedagogy - Dzhuraboeva Ziroat Rakhimberdieva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, the role of morality in educating young people, forming them to look at life with a deep and healthy spirit. Morality is the feeling of moral relations that embody before human eyes. Understanding the rules of ethics. Moral views of great thinkers. The methods of moral education are widely covered.